A comparative melodic analysis on pop country songs between two songwriters of different eras case study: Diane Warren, how do i live & Taylor Swift, love story / Wan Nurzawani Wan Abdullah - Wan Abdullah, Wan Nurzawani (2012)
Each and every one of us lived our everyday lives with skills. Some skills are naturally given and some skills are required through study and practice, such as cooking, playing sports, and learning to speak a new language that requires studying. However, there are skills that not all of us have or given. This skill is songwriting. The combination of two skills which is to practice and perhaps through the genetics. When listening to music, many people do not know the difference between a composer and a songwriter. Firstly, a composer does both, writes and arranges the music and a songwriter is a person who writes the music and lyrics to individual songs.